THE EFFECT OF TRAINING ON THE ROLE AND FUNCTION OF THE HEAD OF OFFICE CARING BASED ON THE IMPLEMENTATION OF STANDARD PRECAUTIONS BY THE IMPLEMENTING NURSE - Deetje Sintje Supit (Jurnal Ilmiah Perawat Manado (Juiperdo), 2021)
Back ground: Standard precautions were part of infection prevention and control project, that was importent thing to implementation at hospital orother public health service, that’s forquality of service patient safety measures, medical staff and family from getting infection risk.The effective ofinfection prevention and control at hospital project describe of good quality service of the hospital as well. The role of head of office as a manager was enormous for nurse in standard precautions implementation. Aimd: This research purposeful to identify effect of role and function of head of office training towards prevention and infection control implementation: standard precautions of the implementing nurses at Hospital Tomohon. Metode: Used to Quasy Experimental pre and post test design. Total sample 78 respondents divide in to two groups: 60 respondents group of intervention, 18 respondents as group of control. Sampling used purposive sampling. Result: showed guideline of head ward (0.179) and duration of work (0.031) were given effect to standard precautions implementations. Conclusion: This research was recommendation role and function head ward worshop as a methode to increase nursing care plan for quarantee quality of patient safety over at hospital.